2020
DOI: 10.4315/0362-028x.jfp-19-273
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella, Listeria monocytogenes, and Indicator Microorganisms on Hass Avocados Sold at Retail Markets in Guadalajara, Mexico

Abstract: Hass avocados may become contaminated with Salmonella and Listeria monocytogenes at the farm and the packing facility or later during transportation and at retail. In Mexico, avocados are frequently sold in bulk at retail markets, where they are stored at room temperature for several hours or days and exposed to potential sources of microorganisms. These conditions may favor the entry, adhesion, survival, and biofilm formation of Salmonella and L. monocytogenes. The aim of this study was to determine the occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The statistical comparisons between the three samples and three locations using one-way ANOVA showed no significant difference (p ≥0.05). The bacterial counts obtained in this research align with the findings of García-Frutos et al 3 , who reported 4.3 to 9.0 CFU/g on Hass avocados sold at retail markets in Guadalajara, Mexico. Similarly, Shiferaw and Kibret 6 reported the mean aerobic mesophilic count of 5.24 log10 CFU/g from avocado peel used to prepare freshly squeezed juices from juice houses of Bahir Dar Town, Northwest Ethiopia.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The statistical comparisons between the three samples and three locations using one-way ANOVA showed no significant difference (p ≥0.05). The bacterial counts obtained in this research align with the findings of García-Frutos et al 3 , who reported 4.3 to 9.0 CFU/g on Hass avocados sold at retail markets in Guadalajara, Mexico. Similarly, Shiferaw and Kibret 6 reported the mean aerobic mesophilic count of 5.24 log10 CFU/g from avocado peel used to prepare freshly squeezed juices from juice houses of Bahir Dar Town, Northwest Ethiopia.…”
Section: Resultssupporting
confidence: 90%
“…However, inoculums were prepared using the whole fruit (i.e., avocado peel, exocarp, and mesocarp). These and other market environmental conditions can lead to higher microbial contaminations in fruit sales in most African retail markets 3 . Other researchers also reported that the variance in microbial loads of fruits might be caused by contamination by microorganisms from the soil, irrigation water, the environment during transit, washing/rinsing water, or process of handling, or it could be part of the fruits' natural flora 3,22-24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 18 L. monocytogenes isolates were evaluated in this study, which were previously obtained from Hass avocados sold at retail markets in Guadalajara, Mexico [12]. Stocks of L. monocytogenes were stored using the protocol described by Avila-Novoa et al [24].…”
Section: Monocytogenes Isolatesmentioning
confidence: 99%
“…In addition, the fresh produce supply chain is complex, with increasing potential sources of L. monocytogenes contamination. For example, contamination from irrigation water, fertilization with contaminated manure and contaminated soil (agricultural practices), cross-contamination from surfaces contaminated with pathogens, food spoilage, improper manipulation by food handlers, or processing fresh produce into fresh-cut products increases the risk of bacterial growth by breaking the fruit’s skin and allowing for the spread and potential growth of any pathogens that may be present [ 3 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%